The thinking, the feeling and the acting about the inclusive education of a teacher of high school - Lima, Marcia Raika e Silva [UNESP] (Editora Univ Leopoldlanum, 2023)
The theoretical lines of this study presents reflections about the meanings of a teacher about the schooling of special education students -PAEE in high school in the context of inclusive education. The objective consisted in: to comprehend what the meanings constituted by a high school teacher about the inclusive education students (PAEE) reveals. This is a qualitative study, which presents the socio-historical theory as a theoretical-methodological basis. For the materialization of this academico study, we opted for the analytical basis of the data collected and recorded in the study: the Cores of Meaning. The analyzes showed that the History teacher revealed that when experiencing the process of schooling PAEE students, in the context of inclusive education, in the context of inclusive education, gives new meanings to their teaching activity, transforming their thinking, feeling and acting
Keywords: Special and inclusive education; Special education students; High school